Ethics teaching in a medical education environment: preferences for diversity of learning and assessment methods. Issue 1 (1st January 2017) - AlMahmoud, Tahra; Hashim, M. Jawad; Elzubeir, Margaret Ann; Branicki, Frank
ABSTRACT: Background : Ethics and professionalism are an integral part of medical school curricula; however, medical students' views on these topics have not been assessed in many countries. Objective:  The study aimed to examine medical students' perceptions toward ethics and professionalism teaching, and its learning and assessment methods. Design : A self-administered questionnaire eliciting views on professionalism and ethics education was distributed to a total of 128 final-year medical students. Results : A total of 108 students completed the survey, with an 84% response rate. Medical students reported frequently encountering ethical conflicts during training but stated only a moderate level of ethics training at medical school (mean = 5.14 ± 1.8). They noted that their education had helped somewhat to deal with ethical conflicts (mean = 5.39 ± 2.0). Students strongly affirmed the importance of ethics education (mean = 7.63 ± 1.03) and endorsed the value of positive role models (mean = 7.45 ± 1.5) as the preferred learning method. The cohort voiced interest in direct faculty supervision as an approach to assessment of knowledge and skills (mean = 7.62 ± 1.26). Female students perceived greater need for more ethics education compared to males (p = < 0.05). Students who claimed that they had experienced some unprofessional treatment had a more limited view of the importance of ethics as a subject (P = 0.001). Conclusion : Medical students viewed ethics education positively and preferred clinically attuned methods for learning.